Bestiary Imagery in Hebrew Manuscripts of the Thirteenth Century - Adam S. Cohen (Religions, 2024)
In medieval bestiaries, knowledge about animals and their behavior is regularly given a Christian moral interpretation. This article explores the use of imagery related to the bestiary tradition in three Hebrew books made around the year 1300, focusing especially on the richly decorated Rothschild Pentateuch (Los Angeles, Getty Museum MS 116). These Hebrew books signal how bestiary knowledge and its visual expression could be adapted to enrich the experience of medieval Jewish reader-viewers, adding to our understanding of Jewish-Christian interactions in medieval Europe.